PENERAPAN TEKNIK EFFLEURAGE MASSAGE DALAM MENGATASI NYERI AFTERPAINS IBU POSTPARTUM DI PUSKESMAS NEGERI LAMA KECAMATAN BILAH HILIR KABUPATEN LABUHANBATU TAHUN 2022 - Herna Rinayanti Manurung; Rosmani Sinaga; Marliani Marliani; Juliana Munthe; Bintang Tobing (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
terine contractions cause pain that have an impact on the application of therapy, including inhibiting breastfeeding, inhibiting mother and child bonding, feeling tired due to felt afterpain, rest disturbances to continuous pain. which causes the risk of postpartum blues and the baby has an impact on the lack of nutritional intake so that it can inhibit the baby's growth and development process. The method used in this activity consists of 3 stages, namely preparation, implementation and evaluation, starting with collecting participants, namely postpartum mothers. From the activities carried out, all participants attended, of which 30 participants registered in this activity, it was found that 23 participants (77%) felt comfortable and 7 participants (23%) did not feel comfortable using the effleurage massage technique. Then the evaluation stage showed the pretest pain level was higher than the post-test pain level, the minimum score was 3 (mild pain) and the maximum score was 8 (severe pain). While the posttest obtained a minimum value of 0 (no pain), and a maximum value of 5 (moderate pain). The conclusion after the effleurage massage technique is that postpartum mothers who experience afterpains are very interested and feel comfortable with the effleurage massage technique